The Rephaim : Sons of the Gods - Yogev, Jonathan (Culture and History of the Ancient Near East, 2021)
In The Rephaim: Sons of the Gods , Jonathan Yogev provides a new theory regarding the mysterious characters, known as "Rephaim," in Biblical and ancient Near Eastern literature. The Rephaim are associated with concepts such as death and the afterlife, divinity, healing, giants and monarchy among others. They appear in Ugaritic, Phoenician and Biblical texts, yet it is difficult to pinpoint their exact function and meaning. This study offers a different perspective, along with full texts, detailed epigraphic analysis and commentary for all of the texts that mention the Rephaim, in order to determine their specific importance in societies of the ancient Levant.